Is stroke smoothness a reliable indicator of fatigue in ergometer rowing? - Caplan, N; Gardner, T. N. (Sports Engineering, 2009)
A measure of stroke smoothness (SS) has been presented previously to indicate the degree to which rowers produce an "ideal" handle force profile that of the positive half of a sine wave [2]. This study aimed to determine the influence of fatigue on SS. Ten male rowers completed a maximal intensity trial. Fast Fourier transform methods were used to calculate SS which was given by the amplitude of the fundamental frequency as a percentage of the sum of the first ten peaks. Visual inspection of the data showed indications of a reduction in movement coordination as a function of fatigue. However, SS did not change significantly between the first, middle and last ten strokes (p = 0.205), despite a 21% reduction in mean power between the start and end of the trial. The results suggested that although the shape of the force profile can qualitatively indicate a reduction in movement coordination, the smoothness of the force profiles remains similar with fatigue.